An insight into numerical investigation of bioreactor for possible oxygen emission on Mars. (2021) - Gupta, Eva; Jee Kanu, Nand; Agrawal, Monika S.; Kamble, Ashwin A.; Shaikh, Alimoddin N.; Kumar Vates, Umesh; Kumar Singh, Gyanendra; Chavan, Sachin S.
Abstract: The present study reviews the possible emission of oxygen to Mars through in situ resource management (ISRM) using advance bioreactor systems. The advances in bioreactor systems (BSs) are proposed through in-depth numerical investigations based on simulations using computational fluid dynamics approaches. The advance BSs is having the potential to support a life system on Mars through efficient conversion of high-grade iron ores via biological reactions and therefore utilizing a sustainable approach. The advancement is made for the photo bioreactor (PBR) having a 20 L flat plate and weight approximately 400 kg for its sustained utilization in a 1400 L biomining reactor. The modification proposed here is effectively demonstrating the significance of agitation velocity on the coefficient of oxygen transfer (kL a) and suggests turbulence flow over transition and laminar flow, as well as Rushton type impeller over inclined paddles and propellers.